Stratigraphy and Ammonite fauna from Campan in North West Munster - Kaplan, U; Kennedy, W; Hiß, M (2005)
The Campanian ammonite faunas of the north-western Münster Basin are systematically and stratigraphically revised. They comprise 39 species, referred to 29 genera. In addition to the type-material of SCHLÜTER (1867; 1871-1876), the specimens mentioned and figured by WIPPICH (1995) and LOMMERZHEIM (1995) are re-examined and partially refigured. The ammonite occurrences are documented in the context of the detailed lithostratigraphy and a foram zonation of the Campanian of the north western Münster Basin and the Campanian standard zones of north Germany. An ammonite stratigraphy for the Münster Basin Campanian is proposed. The basal Lower Campanian remains unzoned. The Placenticeras bidorsatum-Zone comprises the central division of the Dülmen Formation. In the upper part the first occurrence of Scaphites hippocrepis III marks the base of the eponymous zone. Scaphites gibbus enters at the base of the Asbeck-Member, Holtwick Formation, and defines the succeeding ammonite zone. The base of the Upper Campanian corresponds to the base of the Coesfeld Formation and the lies immediately below the base of the Beckum Member and the entry of several species of Hoplitoplacenticeras. The lower part of the Coesfeld Formation corresponds to the Hoplitoplacenticeras vari Zone, the middle part to the Trachyscaphites spiniger-Zone, and the upper part already belongs to the lower Bostrychoceras polyplocum Zone, which also includes the Baumberge Formation excluding the highest part, which lacks ammonites, and remains undated in ammonite terms.